Marketing for Higher Education Institution: A Review and Theoretical Framework - Adrianto, Ega; Suharyanti, Yosephine (Universitas Atma Jaya Yogyakarta, 2024)
A higher education institution (HEI) builds its quality throughout the process, from student admission to graduation. One of the critical points in the admission process, by which the applicants are selected, is the number of applicants being selected. To get a large number of applicants, an HEI undertakes marketing programs. Many studies on HEI marketing discuss factors differently, depending on the case and the viewpoints or the objectives. This study reviews 52 articles on HEI marketing to get general insights and develop a theoretical framework that is expected to be beneficial for HEI practitioners to design their marketing programs and for researchers to get a general model to be referred to. The insights from the review are, first, the development of modified marketing mix 3P1Q (quality, price, promotion, place) for HEI marketing, which is adapted from marketing mix 4P. The second insight is that the focus of HEI marketing discussion has shifted because of the COVID-19 pandemic, regarding the disruption and the intense use of digital technology. This phenomenon could help interested parties predict the future of HEI marketing. The result of this study is a comprehensive theoretical framework of HEI marketing that integrates HEI attributes, HEI marketing factors, HEI marketing impacts, and the relationships among those elements.